2017
DOI: 10.1016/j.jecp.2017.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Are there signature limits in early theory of mind?

Abstract: Current theory-of-mind research faces the challenge of reconciling two sets of seemingly incompatible findings: Whereas children come to solve explicit verbal false belief (FB) tasks from around 4years of age, recent studies with various less explicit measures such as looking time, anticipatory looking, and spontaneous behavior suggest that even infants can succeed on some FB tasks. In response to this tension, two-systems theories propose to distinguish between an early-developing system, tracking simple form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
2
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 41 publications
2
48
2
1
Order By: Relevance
“…The toddlers reacted differently to the agent's true versus false belief only when aspectuality was not involved in the task. This pattern was taken as an indication of conceptual deficits in infants and is in line with the finding that below the age of two, they are capable of tracking mental states and can master implicit FB tasks as long as an understanding of aspectuality or of other propositional attitudes is not necessary to pass the test [22][23][24][25].…”
Section: Early Tomsupporting
confidence: 68%
See 1 more Smart Citation
“…The toddlers reacted differently to the agent's true versus false belief only when aspectuality was not involved in the task. This pattern was taken as an indication of conceptual deficits in infants and is in line with the finding that below the age of two, they are capable of tracking mental states and can master implicit FB tasks as long as an understanding of aspectuality or of other propositional attitudes is not necessary to pass the test [22][23][24][25].…”
Section: Early Tomsupporting
confidence: 68%
“…A recent study revealed the significance of another characteristic of implicit ToM tasks. Fizke et al [22] tracked the helping behavior of 2-to-3-year-old children in two versions of a FB task: one version included aspectuality whereas the other version of the task did not. Aspectuality denotes incompatible beliefs about an object or a person under two different aspects, for example knowing the person Clark Kent as himself versus knowing him as Superman without being aware of his private identity.…”
Section: Early Tommentioning
confidence: 99%
“…However, a recent study by Fizke and colleagues would appear to be at odds with this pattern of positive findings (Fizke, Butterfill, van de Loo, Reindl, & Rakoczy, 2017). In this study, 2.5-year-olds were tested in a non-elicited-response task modeled after the helping paradigm devised by Buttelman, Carpenter, and Tomasello (2009).…”
Section: Discussionmentioning
confidence: 86%
“…Accordingly, they can accurately anticipate an agent's action in change-of-location false-belief tasks, the paradigms most commonly used in research with human infants and nonhuman animals. Critically, the signature limit of such a minimal system is its inability to track genuine beliefs about object identity (36,37). Testing this limitation in the future will be important for precisely specifying the representational mechanisms underlying action anticipation in both human and nonhuman primates.…”
Section: Discussionmentioning
confidence: 99%